Activation of LINE-1 Retrotransposon Increases the Risk of Epithelial-Mesenchymal Transition and Metastasis in Epithelial Cancer - Rangasamy, D. (Curr Mol Med, 2015)
Epithelial cancers comprise 80-90% of human cancers. During the process of cancer progression, cells lose their epithelial characteristics and acquire stem-like mesenchymal features that are resistant to chemotherapy. This process, termed the epithelial-mesenchymal transition (EMT), plays a critical role in the development of metastases. Because of the unique migratory and invasive properties of cells undergoing the EMT, therapeutic control of the EMT offers great hope and new opportunities for treating cancer. In recent years, a plethora of genes and noncoding RNAs, including miRNAs, have been linked to the EMT and the acquisition of stem cell-like properties. Despite these advances, questions remain unanswered about the molecular processes underlying such a cellular transition. In this article, we discuss how expression of the normally repressed LINE-1 (or L1) retrotransposons activates the process of EMT and the development of metastases. L1 is rarely expressed in differentiated stem cells or adult somatic tissues. However, its expression is widespread in almost all epithelial cancers and in stem cells in their undifferentiated state, suggesting a link between L1 activity and the proliferative and metastatic behaviour of cancer cells. We present an overview of L1 activity in cancer cells including how genes involved in proliferation, invasive and metastasis are modulated by L1 expression. The role of L1 in the differential expression of the let-7 family of miRNAs (that regulate genes involved in the EMT and metastasis) is also discussed. We also summarize recent novel insights into the role of the L1-encoded reverse transcriptase enzyme in epithelial cell plasticity that suggest it might be a potential therapeutic target that could reverse the EMT and the metastasis-associated stem cell-like properties of cancer cells.